Programma: 15 april Daryll-ann, Treble Spankers; 16 april Big Chief; 19 april The Klezmatics; 20 april EMF; 21 april Tshala Muana, Swede Swede
Programma: 15 april Daryll-ann, Treble Spankers; 16 april Big Chief; 19 april The Klezmatics; 20 april EMF; 21 april Tshala Muana, Swede Swede.